La conformità della volontà umana con la Volontà di Dio da una prospettiva biblica e patristica, negli autori dei primi dodici secoli - Mestre, Alberto (Alpha omega, 2014)
The theme of the conformity of man’s will to God’s will is somewhat neglected in current theological scholarship. Although it could seem like an exclusively spiritual theme, this article will show that throughout history it was also a genuinely moral issue. The article approaches the question first in Matthew’s Gospel. This brief yet important biblical study prepares the ground for a study of the theme in some Patristic and Medieval authors.